Granulome à cellules géantes: à propos d'une forme centrale et d'une forme périphérique - Robert DACCACHE (International Arab Journal of Dentistry (IAJD), 2017)
Giant cell granulomas and peripheral granulomas are 2 large entities of giant cell tumors. The giant cell granuloma in the bone is called the giant cell granuloma. It is common among young people (21%). Granulomas occurring at edentulous alveolar ridges or gums are called giant cells peripheral cells granuloma, occurring more frequently in adults. Their etiologies are multifactorial; the diagnosis is made based on clinical, radiological particularities, and confirmed by anatomo-histopathology. Treatment is usually surgical, but in some cases it is associated with drug therapy.Two cases are described in the present article, one central granuloma occurring in a 5-year-old girl and the other, peripheral, occurring in a 62-year-old woman. The two cases treated surgically did not recur, 6 years after surgery.